Illegal Migration and Gender in a Global and Historical Perspective - Quispel, Chris; Lucassen, Leo; Schrover, Marlou; van der Leun, Joanne (Amsterdam University Press, 2008)
Two issues come to the fore in current debates over migration: illegal migration and the role of gender in illegal migration. This incisive study combines the two subjects and views the migration scholarship through the lens of the gender perspective, investigating definitions of citizenship and the differences in mechanisms of inclusion and exclusion for men and women, producing a comprehensive account of illegal migration in Germany, the Netherlands, Great Britain, the Soviet Union, Mexico, Malaysia, the Horn of Africa and the Middle East over the nineteenth- and the twentieth centuries.